Harmonization of Regulations for Issuing Duplicate Marriage Certificates at the East Banjarmasin KUA: Harmonisasi Regulasi Penerbitan Duplikat Buku Nikah di KUA Banjarmasin Timur - Normadina, Najwa (Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2025)
This study examines the implementation of issuing duplicate marriage books and marriage certificate excerpts at the Office of Religious Affairs (KUA) of Banjarmasin Timur District in relation to the application of the Minister of Religious Affairs Regulation Number 30 of 2024 concerning Marriage Registration. The main problem of this research lies in the inconsistency between the new regulation and its implementation at the KUA level, where some administrative practices still refer to outdated provisions. This study uses a juridical-normative approach with a descriptive qualitative method through literature review, document analysis, and limited interviews with KUA officials. The findings show that the issuance process has not been fully aligned with PMA Number 30 of 2024 due to limited understanding of new procedures and the absence of uniform digital verification systems. However, KUA Banjarmasin Timur continues to strive for effective service and data integrity in fulfilling public administrative needs. The study emphasizes the importance of regulatory harmonization, digital-based data management, and capacity building for KUA officers to ensure legal certainty and efficiency in marriage administration across Indonesia.